Analysis Of Calculation And Withduction Of Pph Article 21 The Salary Of Civil Servants - dahrani dahrani (International Journal Reglement & Society (IJRS), 2021)
Income Tax Article 21 is a tax on income in the form of salaries, wages, honorarium, allowances, and other payments received or obtained by domestic individual Taxpayers in connection with work or position, services and activities. The Forestry Service of North Sumatra Province carries out salary payments and also cuts Article 21 Income Tax for its employees. The purpose of this study was to analyze and evaluate the suitability of the calculation and withholding of Article 21 income tax carried out by the agency against the Taxation Law and also to determine the imposition of the PTKP tariff applied by the Forestry Service of North Sumatra Province. The approach used in this study uses a descriptive approach, data collection techniques used in the form of documentation and interview results. The data analysis technique used is to conduct a survey at the research site to obtain data and analyze the data to draw conclusions and compare the problem with theories to support the problem. The results of the research obtained at the Forestry Service of North Sumatra Province, namely in calculating and withholding Income Tax Article 21 still found errors in calculating employee PTKP rates, the Forestry Service did not use the actual employee status in calculating employee income taxes. As a result of this error, the calculation of PPh Article 21 resulted in a difference in payment and the reported tax was greater than the tax payable that should have been.